KUFRI UDAY: AN EARLY MATURING RED SKIN POTATO VARIETY - Luthra, Satish Kumar (Potato Journal, 2023)
ABSTRACT: Kufri Uday is an early maturing, main season, high yielding table potato variety suitable for cultivation in North Indian plains (Northern, Central, and Eastern plains). It is a clonal selection from the cross between CIP387521.3 √ Aphrodite. Its plants are medium tall and vigorous with field resistance to late blight. It produces attractive red coloured ovoid tubers with shallow eyes, yellow flesh, and a mealy texture. The new variety possesses 18-19% tuber dry matter and very good keeping quality. It is fertilizer responsive and capable of yielding 36–38 t/ha under optimum agronomical practices.